A new trainers - Hunt, Roderick (Oxford Oxford university press, 2011)
Kipper gets a new pair of trainers and is very excited to try them out. But when he wears them, things don$1 (Bt go as expected, leading to some funny little mishaps before everything is sorted out.s
Children try out new trainers, encounter small surprises, and learn through playful mishaps in a simple familiar setting.
Keywords: English